2021
DOI: 10.3390/tropicalmed6030113
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Symptoms in Post-COVID-19 Patients Attending Follow-Up OPD at Sukraraj Tropical and Infectious Disease Hospital (STIDH), Kathmandu, Nepal

Abstract: The long-term effects of COVID-19 among survivors is a matter of concern. This research aimed to study persistent symptoms in post-COVID-19 patients attending a follow-up clinic at a tertiary care hospital in Nepal. All patients, presenting to the outpatient clinic during the study duration of six weeks, with history of positive reverse transcriptase- polymerase chain reaction for severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) at least two weeks prior to presentation, were included. The duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
(21 reference statements)
1
21
2
Order By: Relevance
“…However, in that study, only 28.1% of patients had cough at hospital admission (26) which was much lower than that in our study (79%) and other studies in China (8,(32)(33)(34)(35). Compared with studies from European and American countries, the prevalence of post-COVID-19 cough in Asian countries seemed to be lower (20-41.9% vs. 27.5-29%) (20)(21)(22)(23)(24)(25)(26)(27)36). It is unclear whether the ethnic difference contributed to the prevalence of cough.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…However, in that study, only 28.1% of patients had cough at hospital admission (26) which was much lower than that in our study (79%) and other studies in China (8,(32)(33)(34)(35). Compared with studies from European and American countries, the prevalence of post-COVID-19 cough in Asian countries seemed to be lower (20-41.9% vs. 27.5-29%) (20)(21)(22)(23)(24)(25)(26)(27)36). It is unclear whether the ethnic difference contributed to the prevalence of cough.…”
Section: Discussioncontrasting
confidence: 86%
“…Our study showed that symptoms of COVID-19 significantly reduced long after discharge, however, approximately one-fifth of patients still presented with at least one symptom, including cough, dyspnea, fatigue and anorexia at the follow-up. The incidence of symptoms in our study is significantly lower compared with previous studies (17,18,(21)(22)(23)26,27). We attributed it to a longer period after discharge, which also implied that COVID-19 infection would rarely cause severe and longterm sequelae.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…At the beginning of the COVID-19 pandemic, little was known about long-lasting symptoms following acute COVID-19. The current state of research now indicates various physical, cognitive, and psychological symptoms in affected patients which persist over weeks or months and depend on disease severity (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). According to current publications, more than 1/3 of patients with acute COVID-19 develop long COVID-19 symptoms (23,(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to neurocognitive symptoms in patients with long-COVID, the results of a meta-analysis found that 45% of hospitalized patients showed symptoms of depression and 47% showed symptoms of anxiety (42). The frequency of depression and anxiety symptoms among COVID-19 patients decreased within several weeks after disease onset but was still present in 9% (26) to 13.6% (17) of patients for anxiety and in ∟20% of patients for depression (26). Younger age, working in the healthcare sector, and female gender seem to be risk factors for depression and anxiety (43).…”
Section: Introductionmentioning
confidence: 99%